Virtual nurse support to enhance antipsychotic adherence in schizophrenia: A South African perspective - Yasmeen Thandar; Nomhle Mvunelo; Deepak Singh; Firoza Haffejee (South African Journal of Psychiatry)
Background: Patients with schizophrenia rely on antipsychotic medication, with adherence being critical for symptom management. Poor adherence leads to relapse, disability and increased healthcare costs.